PROCESS IMPROVEMENT AND INVESTMENT PROFITABILITY IN PRODUCTION CONTEXT: A Case of Electrical Industry, ABB Oy Transformers, Vaasa Finland - Manner, Matti (My University, 2006)
The purpose of the thesis was to study the profitability of an automation investment prepared for production process. Another objective was to create a simulation model for evaluating investments in production processes, which could be used in other improvement investments as well. As the industrial competition environment and the pressure from interest groups is increasingly demanding for better productivity and profit margins, companies are forced to improve their operations and furthermore forced to make the right decisions when answering these requirements. This study aims to find the most beneficial ways of estimating the investments in production context, and to create a tool to support decision-making. Although methods for investment appraisal have been studied extensively in the past, research has mostly concentrated on economical factors related to investment evaluation, and less sort of comprehensive studies have been made. Moreover simulation-modelling as a tool in investment analysis has not received enough attention. The primary method was a single case study. The research process consisted on the one hand of a thorough literature review on the subject, and on the other hand of an empirical study of the case company’s automation investment. The study was a combination of exploratory and descriptive research, and further it contained the elements of both deduction and induction. The empirical part of the research was covered by thorough analysis of data available in company’s data system, and brainstorming in expert group. One of the main findings of the study was that simulation-modelling methods are beneficial in conducting analysis of investments to production context. Thorough evaluations of possible investments are required and for these demands companies should have a formal method, in order to have comparable studies of different investments. A simulation model is a useful tool particularly if it enables the assessor to adjust the parameters and test different what-if states by running scenario and risk analysis.
Keywords: Investment profitability; cost-benefit analysis; simulation; production improvement; automation; fi=Tuotantotalous|en=Industrial Management|